2011
DOI: 10.3945/jn.109.114330
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Snacking in Energy Balance: a Biobehavioral Approach,

Abstract: Snacking is often presumed to contribute to obesity, but to date, studies have not demonstrated such a causal relationship, probably because a clear definition of snacking is still elusive. The usual one, i.e. any intake between traditional meals, has no physiological basis. Moreover, because some evidence suggests that frequent meals may prevent overweight, any confusion between snacks and meals may mask the deleterious effect of snacks on energy balance. Therefore, we developed a biobehavioral approach to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
88
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 31 publications
2
88
0
3
Order By: Relevance
“…Moreover, it has been proposed that snacks between main meals do not generate extra signals of satiety (30) . Thus, snacking may lead to a positive energy balance because it exerts a weaker satiety effect than consumption of the same foods during meals and its energy content is not compensated for at the next meal (10) . Overweight and obesity, especially abdominal obesity, are the result of a chronic positive energy balance (31) which is also related to other MetS individual criteria such as dyslipidaemia, hyperglycaemia and, consequently, hypertension (31,32) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been proposed that snacks between main meals do not generate extra signals of satiety (30) . Thus, snacking may lead to a positive energy balance because it exerts a weaker satiety effect than consumption of the same foods during meals and its energy content is not compensated for at the next meal (10) . Overweight and obesity, especially abdominal obesity, are the result of a chronic positive energy balance (31) which is also related to other MetS individual criteria such as dyslipidaemia, hyperglycaemia and, consequently, hypertension (31,32) .…”
Section: Discussionmentioning
confidence: 99%
“…Snack consumption has recently been highlighted as one of these potential unhealthy eating habits (7)(8)(9) . The frequency of snack consumption is relatively high, especially among populations from Western countries (10) . Although there are some studies that have shown an association between snacking and obesity (7,(10)(11)(12) , the relationship of this eating habit with MetS is not well established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Snacking is defined as an episode of food consumption occurring outside the context 35 of typical main meals, including all food and beverage items (Chapelot, 2011). Snack foods 36 are readily available in a variety of settings, including the school environment (Savige,37 Macfarlane, Ball, Worsley, & Crawford, 2007), and therefore snacking is highly prevalent, 38 particularly among children and adolescents.…”
Section: Introduction 32mentioning
confidence: 99%
“…Consequently, snacking contributes significantly 41 to daily energy and nutritional intake in young people (Ovaskainen et al, 2006), which is 42 potentially problematic and may lead to overconsumption of calories, free-sugars and 43 nutrient-poor, energy-dense foods. Indeed, while the health effects associated with such 44 dietary behaviours are well known (Chapelot, 2011) the promotion of more healthful snacks 45 could benefit overall dietary intake, nutritional status and actually act as a marker for 46 healthier eating habits. 47…”
Section: Introduction 32mentioning
confidence: 99%